Eltrombopag for the treatment of refractory connective tissue disease-related thrombocytopenia: a pilot study of 52 cases - Siying Deng; Bei Wang; Ziwei Hu; Shaozhe Cai; Lingli Dong (Arthritis Research & Therapy)
Abstract Background The objective of this study was to investigate the therapeutic effectiveness and safety profile of Eltrombopag, a thrombopoietin receptor agonist, as prolonged therapy in refractory CTD-ITP patients. Methods We conducted a pilot observational study of Eltrombopag in CTD-ITP patients who were unresponsive to or intolerant of conventional medications. Eltrombopag was administered orally at 25–75 mg/qd and adjusted on the basis of tolerance and efficacy until a minimum dosage of 25 mg/qd was reached. Clinical and laboratory data were collected and analysed monthly. The therapeutic response, relapse, and adverse events during the follow-up were also reviewed and evaluated. Results Fifty-two patients were enrolled and followed monthly for a median of 6 months. Thirty-six (90%) patients achieved durable overall remission. The remission rates were 67.5% at month 1, 87.5% at month 2, 97.5% at month 3, and 95% at month 6. The platelet count of the patients improved significantly, with the median reaching 50 × 109/L within 2 weeks (p = 0.003). Disease activity indices were reduced in SLE and pSS patients (p = 0.016), allowing glucocorticoid tapering (p = 0.004). One patient had no response, four relapsed, and fifteen (28.8%) experienced clinically relevant adverse events. In the analyses, protopathy, comorbidity, and prior treatment were associated with efficacy. Conclusions For refractory CTD-ITP patients, Eltrombopag demonstrated significant clinical improvement, safety, and a steroid-sparing effect with prolonged use. Patient characteristics at baseline may affect treatment efficacy.